ZBTB16 and metabolic syndrome: a network perspective - Šeda, O; Šedová, L; Včelák, J; Vaňková, M; Liška, F; Bendlová, B (Physiological research, 2017)
Metabolic syndrome is a prevalent, complex condition. The search for genetic determinants of the syndrome is currently undergoing a paradigm enhancement by adding systems genetics approaches to association studies. We summarize the current evidence on relations between an emergent new candidate, zinc finger and BTB domain containing 16 (ZBTB16) transcription factor and the major components constituting the metabolic syndrome. Information stemming from studies on experimental models with altered Zbtb16 expression clearly shows its effect on adipogenesis, cardiac hypertrophy and fibrosis, lipid levels and insulin sensitivity. Based on current evidence, we provide a network view of relations between ZBTB16 and hallmarks of metabolic syndrome in order to elucidate the potential functional links involving the ZBTB16 node. Many of the identified genes interconnecting ZBTB16 with all or most metabolic syndrome components are linked to immune function, inflammation or oxidative stress. In summary, ZBTB16 represents a promising pleiotropic candidate node for metabolic syndrome.
Keywords: genové regulační sítě; Animals; Oxidative Stress; zinkové prsty; Humans; protein promyelocytické leukemie s motivem zinkového prstu; Metabolic Syndrome; lidé; zvířata; Zinc Fingers; Insulin Resistance; oxidační stres; Promyelocytic Leukemia Zinc Finger Protein; metabolický syndrom; Gene Regulatory Networks; inzulinová rezistence